Differences in sarcopenia prevalence between upper-body and lower-body based EWGSOP2 muscle strength criteria: the Tromsø study 2015–2016 - Johansson, Jonas; Strand, Bjørn Heine; Morseth, Bente; Hopstock, Laila Arnesdatter; Grimsgaard, Sameline (BMC Geriatrics, 2020)
Background - The European Working Group on Sarcopenia in Older People (EWGSOP2) recommends grip strength and chair stand tests to be used as primary defining measures. It is unclear how either test affects prevalence estimates. Methods - This cross-sectional study involved 3498 community-dwelling participants (40–84 years) from the 7th Tromsø Study survey (2015–2016). We used grip strength, five-repetition chair stands, four-meter Walk Speed Test, Timed-Up-and-Go (TUG) and Dual-Energy X-ray Absorptiometry measurements. Data were analyzed using multiple linear regression models and ROC-curves. Results - Probable and confirmed sarcopenia prevalence was 1.3 and 4.4% based on grip strength and chair stands, respectively. There was very low agreement between grip strength and chair stand cut-offs (κ = 0.07), with only 4.3% of participants defined as having probable sarcopenia overlapping in the two criteria. Participants with grip strength-based sarcopenia had lower mean height, weight, waist circumference, and appendicular lean mass relative to body height (ALM height 2 ) than non-sarcopenic participants (all p < 0.001), after adjusting for multiple covariates. Conversely, participants with chair stand-based sarcopenia had similar height, higher weight, waist circumference and body fat% compared to non-sarcopenic participants (all p < 0.05). Area-under-curves (AUCs) for TUG-time were significantly larger when using chair stand instead of grip strength cut-offs (0.86, 95% CI 0.84–0.89 vs. 0.75, 95% CI 0.69–0.83). Conclusions - Using chair stands instead of grip strength more than doubled probable sarcopenia prevalence across all ages. The two measures defined individuals of contradictory anthropometrics, body composition, and dissimilar physical function to have probable sarcopenia. Researchers should further evaluate the consequences of using different strength measures in the EWGSOP2 definition to classify sarcopenia.